George Thomas Washington papers - Washington, George Thomas; Washington, George Thomas
Correspondence, speeches, writings, personal and office files, legal memoranda, memorabilia, photographs, and other papers relating chiefly to Washington's service as an attorney in the U.S. Dept. of Justice and as chief of U.S. lend-lease operations in the Middle East and head of American economic missions in Iran and Iraq during World War II. Subjects include the labor conditions of coal miners, price controls, congressional investigations of subversives, resident aliens and national security, the 1942 trial of Nazi saboteurs, and treatment of German war criminals. Includes drafts of Washington's book Corporate Executives' Compensation (1942) and other writings chiefly on legal topics. Correspondents include Dean Acheson, Tom C. Clark, Livingston L. Short, Edward R. Stettinius, Robert S. Stevens, and Harry S. Truman.
Judge, official in the U.S. Office of the Attorney General, and law professor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Clark, Tom C. -- 1899-1977 -- Correspondence; Short, Livingston L. -- Correspondence; Stettinius, Edward R. -- 1900-1949 -- Correspondence; Stevens, Robert S. -- 1888-1968 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; United States. -- Department of Justice. -- Office of the Attorney General; Aliens -- United States; Coal miners -- United States; Coal mines and mining -- United States; Executives -- Salaries, etc; Labor -- United States; Law; Lend-lease operations (1941-1945); National security -- United States; Nazis; Price regulation -- United States; Sabotage; Subversive activities -- United States; War criminals -- Germany; World War, 1939-1945 -- Economic aspects; World War, 1939-1945 -- Economic aspects -- Iran; World War, 1939-1945 -- Economic aspects -- Iraq; World War, 1939-1945 -- Economic aspects -- Middle East; Iran -- Commerce -- United States; Iraq -- Commerce -- United States; United States -- Commerce -- Iran; United States -- Commerce -- Iraq; Educators; Jurists; Public officials